Young religious leaders in modern Asia: beyond secularism, online and offline - Nghiem, Thao (2022)
The younger generation in Asian societies no longer simply accept that being modern and distant from religion means a better form of governance and the way forward. It is necessary to rethink the role of religion in public life and to harness technology for more conversations and experience-sharing among different communities and faiths to celebrate diversity and forge social cohesion for the common good.